Optimasi Pengelolaan Keuangan dan Memperkuat Branding dengan Teknologi Kecerdasan Buatan bagi UMKM - Apriliany, Ananda Putri; Choiria, Aprina; Septiana, Anisya Eka; Raikhan, Muhammad; Apriyani, Fauziah; Wulandari, Try (Universitas Nusantara PGRI Kediri, 2024)
Community service journal that aims to optimize financial management and strengthen UMKM branding through the use of Ai technology. This activity is carried out by prioritizing the use of Ai-based tools and systems in creating logos in order to strengthen brand image, as well as designing financial management strategies. The method used is a question and answer lecture that includes 4 stages, namely observation, socialization, demonstration, and evaluation. The results of this implementation show an increase in participant knowledge in financial management, by calculating production costs, calculating profits, and calculating VAT. In addition, the use of Ai in branding strategies also shows an increase in knowledge in creating logos for brand recognition. The results show that the use of Ai technology can be an effective solution to increase UMKM performance, thereby helping to encourage local economic growth.